Changes in the uses and gratifications of virtual communications for Kansas State Research And Extension agents during the COVID-19 pandemic - Messerla, Katie (Kansas State University, 2022)
In late 2019, an unknown version of pneumonia was reported in Wuhan, Hubei Province, China. This version of pneumonia was later named COVID-19, and on March 21, 2020, the World Health organization declared COVID-19 a pandemic. The pandemic has affected life for people globally due to mask wearing, social distancing, lockdown, and work-from-home orders. To slow the spread of the virus, many people had to adjust to working from home, resulting in changes to their use of virtual communications for work and social interaction. Uses and gratifications theory, a theory developed by Katz and Blumler in the early 1940s, states that audiences are active rather than passive consumers of media. Uses and gratifications theory examines what motivations and rewards cause audiences to use media, including how individuals use virtual communications channels in the office. Uses and gratifications theory can apply to many facets of communications, including workplace communication. Kansas State Research and Extension has undergone many changes due to the COVID-19 pandemic. Extension agents were required to work from home temporarily and had to adapt to technology changes to continue workplace and external communication. The purpose of this study was to determine changes in the use of virtual communications used by Kansas State Research and Extension agents’ internal communications as a result of the COVID-19 pandemic. Three research questions were used to guide this study including Q1: To what extent has KSRE agents’ use of Zoom, texting by phone, Skype, Slack, and Microsoft Teams changed as a result of the COVID-19 pandemic? Q2: How did their use of virtual communication change in how it satisfied KSRE agents’ needs to communicate internal information in the workplace? Q3: How did virtual communications satisfy social gratifications in the office for KSRE agents before March 2020 to the time of the survey (July 2022)? This study was guided by uses and gratifications theory to understand what virtual communications channels Extension agents used for internal communications and what workplace needs virtual communications satisfied. This study utilized a quantitative Qualtrics survey (n = 99). Through a series of side-by-side before and after matrix questions, agents indicated what tasks they use virtual communications for, and what gratifications they receive from virtual communications channels before and two years into the pandemic. Before the COVID-19 pandemic, texting was the main channel of virtual communication used to communicate within the office. Two years into the COVID-19 pandemic, Zoom, texting, and Microsoft Teams are the virtual communications channels most used by agents. While survey results show an increased use and appreciation for virtual communications, agents indicated a preference for in-person communication both before the COVID-19 pandemic and two years into the COVID-19 pandemic for social matters like developing workplace friendships, relationships, and connections. Two years into the COVID-19 pandemic, agents have used virtual communications more than before the pandemic to obtain information, schedule meetings, share work progress and maintain communications when working remotely. Recommendations include Kansas State University Research and Extension support training on Zoom and Microsoft Teams to help agents move toward consistent and efficient use of each virtual communication channel. This study also recommends Extension administration use these forms of virtual communication to communicate with agents when they are not able to meet in person.
Keywords: Extension communication; Uses and gratifications theory; COVID-19; Virtual communication; Organizational communication